Analysis of Daily Visual Habits in a Presbyopic Population - Filomena Ribeiro; Tiago B. Ferreira; Diana Silva; Ana Cláudia Matos; Sylvia Gaspar; David P. Piñero (Journal of Ophthalmology)
Purpose. To evaluate and report the visual habits and requirements of a sample of presbyopic patients using an advanced sensor. Methods. Transversal study collecting clinical data from 40 presbyopes candidates for presbyopia-correction intraocular lens (IOL) implantation with mean age of 61.0 years (43–80 years). A complete ophthalmological examination was performed in all patients including visual, refractive, an ocular biometric analysis. Furthermore, patients were instructed about the use of the Vivior Monitor system (Vivior AG, Zürich, Switzerland), which consists of a series of sensors attached to the rim of the patient’s glasses that capture information about the visual behavior of the patient. This device was worn for a period of 36 hours or more. The data collected were transferred to a database and analyzed. Results. Mean percentages of time dedicated to distance, intermediate, and near vision were 27.25 ± 11.93% (5–65%), 30.23 ± 9.36% (12–50%), and 42.53 ± 14.96% (13–78%), respectively. Mean percentages of time performing activities under photopic, mesopic, and scotopic conditions were 37.08 ± 23.20% (5–87%), 33.65 ± 13.84% (6–67%), and 29.28 ± 17.03% (4–65%). The percentage of time with digital screens ranged from 2% to 48%. Age was significantly correlated with the percentage of time dedicated to distance vision (r = 0.317, p=0.047) and to activities performed under photopic conditions (r = −0.344, p=0.030). Conclusions. Distance and illumination conditions used to perform different daily life visual activities vary significantly among presbyopes, with a trend to the dedication of more time to intermediate and near visual activities performed under photopic and mesopic conditions. Data interpretation should be done with care until a proper validation of the device used.